2020
DOI: 10.1038/s41598-020-71968-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of effector candidate genes of Rhizoctonia solani AG-1 IA expressed during infection in Brachypodium distachyon

Abstract: Rhizoctonia solani is a necrotrophic phytopathogen belonging to basidiomycetes. It causes rice sheath blight which inflicts serious damage in rice production. The infection strategy of this pathogen remains unclear. We previously demonstrated that salicylic acid-induced immunity could block R. solani AG-1 IA infection in both rice and Brachypodium distachyon. R. solani may undergo biotrophic process using effector proteins to suppress host immunity before necrotrophic stage. To identify pathogen genes expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…These results suggested that the R. solani AG-1 IA would have a short biotrophic interaction at the early infection process on B. distachyon. This idea was also supported by the expression of the effector-like genes at the early infection stage up to 24 h prior to the formation of the necrotic lesions [36]. On the contrary, we also found that the exogenous application of BTH (acibenzolar-S-methyl) induced susceptibility of this pathogen in B. distachyon.…”
Section: Discussionsupporting
confidence: 71%
“…These results suggested that the R. solani AG-1 IA would have a short biotrophic interaction at the early infection process on B. distachyon. This idea was also supported by the expression of the effector-like genes at the early infection stage up to 24 h prior to the formation of the necrotic lesions [36]. On the contrary, we also found that the exogenous application of BTH (acibenzolar-S-methyl) induced susceptibility of this pathogen in B. distachyon.…”
Section: Discussionsupporting
confidence: 71%
“…More recently, fungal small RNAs encoded by Fusarium graminearum were shown to suppress host defence gene expression [103] and a similar approach could also be a feature of the Magnaporthe grisea infections [104]. B. distachyon also lent itself to the development of an infection system with Rhizoctonia solani, based on which 61 secreted protein effectors were identified that could manipulate the host [105] via WRKY transcription factors BdWRKY38 and BdWRKY44 [106,107].…”
Section: Open Accessmentioning
confidence: 99%
“…Rice sheath blight, caused by Rhizoctonia solani Kihn ( R. solani ), has a widespread impact on rice production worldwide (Li et al 2021 ; Molla et al 2020 ). It can reduce rice yields by up to 50% and dramatically affect rice quality, threatening global food security (Abdelsalam et al 2020 ; Singh et al 2019 ). The disease is difficult to control due to lack of resistant rice cultivars and favorable conditions for R. solani , such as warm temperatures and high humidity (Kouzai et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%